Simultaneous knockout of multiple LHCF genes using single sgRNAs and engineering of a high‐fidelity Cas9 for precise genome editing in marine algae. Issue 8 (9th April 2021) - Sharma, Amit K.; Nymark, Marianne; Flo, Snorre; Sparstad, Torfinn; Bones, Atle M.; Winge, Per
Summary: The CRISPR/Cas9 system is an RNA‐guided sequence‐specific genome editing tool, which has been adopted for single or multiple gene editing in a wide range of organisms. When working with gene families with functional redundancy, knocking out multiple genes within the same family may be required to generate a phenotype. In this study, we tested the possibility of exploiting the known tolerance of Cas9 for mismatches between the single‐guide RNA (sgRNA) and target site to simultaneously introduce indels in multiple homologous genes in the marine diatom Phaeodactylum tricornutum . As a proof of concept, we designed two sgRNAs that could potentially target the same six light‐harvesting complex (LHC) genes belonging to the LHCF subgroup. Mutations in up to five genes were achieved simultaneously using a previously established CRISPR/Cas9 system for P. tricornutum . A visible colour change was observed in knockout mutants with multiple LHCF lesions. A combination of pigment, LHCF protein and growth analyses was used to further investigate the phenotypic differences between the multiple LHCF mutants and WT. Furthermore, we used the two same sgRNAs in combination with a variant of the existing Cas9 where four amino acids substitutions had been introduced that previously have been shown to increase Cas9 specificity. A significant reduction of off‐target editing events was observed, indicating that the altered Cas9 functioned as a high‐fidelity (HiFi) Cas9 nuclease.